JOINT PATTERNS IN GRANITE AND ITS RELATIONSHIP WITH ITS SLOPE FAILURE: BUKIT LANJAN ROCK SLIDE REVISITED - Sapari, Nasiman (2011)
Geological condition is an important factor that determines slope stability particularly for engineering projects such as the construction of dams and highways involving hilly terrains. Granite, the rock that is considered as having massive structures, is often assumed to be a stable and suitable basement for any construction projects. However, many engineering failures happened arising from construction on granite terrain including the rock slide at Bukit Lanjan in 2003. The incident of Bukit Lanjan rock slide resulted in an economic lost of about RM836 million due to the NKVE highway closure for 6 months. This paper presents the finding of a detail joint pattern analysis of granite in Bukit Lanjan and the surrounding areas. A total of 741 joint planes were measured from the area covering about 3 km radius from the point of rock slide at Bukit Lanjan. The joint planes were plotted on stereonet and contour lines were drawn to indicate the orientation densities. Results of the density distribution show that the Bukit Lanjan area has 3 predominant joint planes with strike and dip orientations of 70/10, 300/85 and 40/80. About 3 km to the north and to the west in Sungai Buloh and Damansara Damai areas the major orientation of joint planes change to 215/60, 135/60 and 305/80. The joint pattern in Bukit Lanjan forms a wedge blocks that became unstable during to slope cutting in NE-SW direction and resulted in a rock slide towards SE. In the northern part, wedge blocks may also be created but the tendency of slide is torwards NW. The different in orientation of the planes is due to its origin from exfoliation joint.